Trust, Incomplete Contracting, and Corporate Innovation - Xie, Fei; Zhang, Bohui; Zhang, Wenrui (Management Science, 2022)
Innovation is a contract-intensive economic activity in a world of incomplete contracts. We show that trust mitigates incomplete contracting and enhances innovation by acting as an informal contracting mechanism. Trust plays an especially important role when formal laws and regulations are lacking, and it promotes innovation by encouraging collaboration and fostering tolerance for failure. Further analyses show that trust also facilitates cross-border technological spillover and innovation collaboration. Overall, our evidence highlights innovation as a key conduit through which trust affects economic growth. This paper was accepted by Gustavo Manso, finance.